Staphylococcal Protein A Is a Key Factor in Neutrophil Extracellular Traps Formation - Hoppenbrouwers, Tamara; Sultan, Andi R.; Abraham, Tsion E.; Lemmens-den Toom, Nicole A.; Hansenová Maňásková, Silvie; van Cappellen, Wiggert A.; Houtsmuller, Adriaan B.; van Wamel, Willem J. B.; de Maat, Moniek P. M.; van Neck, Johan W. (Frontiers in Immunology, 2018)
Staphylococcus aureus are strong inducers of neutrophil extracellular traps (NETs), a defense mechanism of neutrophils against pathogens. Our aim was to explore the role of Protein A in S. aureus-induced NETosis. We determined the Protein A production of four different S. aureus strains and found a direct relationship between the degree of NETosis induction and Protein A production: strains producing higher concentrations of Protein A evoke significantly more NETs. A S. aureus strain in which Protein A as well as a second binding protein for immunoglobulins (Sbi) have been knocked-out (ΔSpA ΔSbi) induced significantly less NETosis than the wild-type strain. NETosis induction by this knockout strain can be rescued by the addition of purified Protein A. Dead S. aureus did not induce NETosis. In conclusion, Protein A is a determinant for NETosis induction by S. aureus.